Proceedings of the SIGCHI Conference on Human Factors in Computing Systems 2010
DOI: 10.1145/1753326.1753635
|View full text |Cite
|
Sign up to set email alerts
|

Pensieve

Abstract: Reminiscing is a valuable activity that people of all ages spontaneously and informally partake in as part of their everyday lives. This paper discusses the design and use of Pensieve, a system that supports everyday reminiscence by emailing memory triggers to people that contain either social media content they previously created on third-party websites or text prompts about common life experiences. We discuss how the literature on reminiscence informed Pensieve's design, then analyze data from 91 users over … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 125 publications
(21 citation statements)
references
References 28 publications
0
17
0
1
Order By: Relevance
“…Archived digital data offer a number of valuable features, such as enabling a digital baby book for young parents [31] or supporting reminiscence through memory triggers [46]. Parents value digital legacies, and are critical of the notion that content like family photos should decay or disappear over time [23].…”
Section: Temporality Onlinementioning
confidence: 99%
See 1 more Smart Citation
“…Archived digital data offer a number of valuable features, such as enabling a digital baby book for young parents [31] or supporting reminiscence through memory triggers [46]. Parents value digital legacies, and are critical of the notion that content like family photos should decay or disappear over time [23].…”
Section: Temporality Onlinementioning
confidence: 99%
“…Odom et al created a system called Photobox, which occasionally prints a randomly-selected photo from a Flickr user's own collection [44] to trigger memories over time. Cosley et al created a system called Pensieve, which supports reminiscence by triggering memories via digital traces [13,46].…”
Section: Temporality Onlinementioning
confidence: 99%
“…Technologies for gathering and managing digital personal items, referred to as life-logging systems, are recommended for reminiscence and reflection [2,9,30,31]. With increasingly more personal content collected by technologies [9], another realm of research sought to understand people's interaction with digital past [1,[32][33][34][35]. Fleck et al identified re-visitation as a fundamental reflection activity that depends on the higher levels of reflection that require an explaining, connecting, and transforming experience [3].…”
Section: Related Workmentioning
confidence: 99%
“…They put forth the research challenge to explore connections within and between these areas, which inspired our direction of study. Areas of focus in this research lie in identifying ways to trigger reminiscence, and to identify the connections and relationships between blogged items [3,32,34].…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation